JURIDICAL REVIEW OF THE MERAH PUTIH COOPERATIVE AND THE ROLE OF THE NOTARY MAKING THE COOPERATIVE DEED (NPAK) IN ITS ESTABLISHMENT BASED ON INDONESIAN COOPERATIVE LAW - Felly Faradina; Zulhendrawan; Dini Dewi Heniarti; Neni Sri Imaniyati; Dhody Ananta Rivandi W (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
As a manifestation of the implementation of Article 33 paragraphs (1) and (4) of the 1945 Constitution of the Republic of Indonesia, the government initiated a community economic empowerment program in early 2025 through the establishment of the "Koperasi Merah Putih" (Red and White Cooperatives). In its initial phase, the government aims to establish up to 80,000 such cooperatives across villages and urban neighborhoods throughout Indonesia. Within this program, the Notary Making Cooperative Deeds (NPAK) plays a crucial role in ensuring the legal validity of these cooperatives' establishments. This study aims to examine the mechanisms involved in the formation of the Koperasi Merah Putih and to analyze the role of NPAK in this process. However, challenges arise for notaries, particularly NPAK, due to certain regulatory differences between the establishment of Koperasi Merah Putih and conventional cooperatives. Employing a normative juridical research method through literature study, this research utilizes an analytical approach to scrutinize the Koperasi Merah Putih and the role of NPAK from theoretical, regulatory, and practical perspectives. The findings reveal that the Articles of the Association of Koperasi Merah Putih differ from those of typical cooperatives in terms of naming conventions, types of business activities, management structures, membership areas, and procedures for obtaining legal entity status.